2017
DOI: 10.1371/journal.pone.0168683
|View full text |Cite
|
Sign up to set email alerts
|

Association of Occupational and Leisure-Time Physical Activity with Aerobic Capacity in a Working Population

Abstract: IntroductionObjective data on the association of maximal aerobic capacity (VO2max) with work related physical activity are sparse. Thus, it is not clear whether occupational physical activity (OPA) contributes to an increase of VO2max. This study examined the association of VO2max with work and non-work related physical activity in a Swiss working population.MethodsIn this cross-sectional study, a total of 337 healthy and full-time employed adults were recruited. Demographic data, height, weight and BMI were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…Occupational and leisure‐time SB may have different health effects due to different patterns of sitting accumulation (eg, duration and repetitiveness) or the context in which SB occurs . Furthermore, recent studies have found that leisure‐time SB had stronger effects on cardiorespiratory and cardiometabolic health compared to occupational SB . To distinguish between accelerometer‐based SB at the workplace and SB in leisure‐time, future studies should capture self‐reported records of daily working hours and use these data as an additional confounder to identify patterns of SB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational and leisure‐time SB may have different health effects due to different patterns of sitting accumulation (eg, duration and repetitiveness) or the context in which SB occurs . Furthermore, recent studies have found that leisure‐time SB had stronger effects on cardiorespiratory and cardiometabolic health compared to occupational SB . To distinguish between accelerometer‐based SB at the workplace and SB in leisure‐time, future studies should capture self‐reported records of daily working hours and use these data as an additional confounder to identify patterns of SB.…”
Section: Discussionmentioning
confidence: 99%
“…14,33 Furthermore, recent studies have found that leisure-time SB had stronger effects on cardiorespiratory and cardiometabolic health compared to occupational SB. 33,34 To distinguish between accelerometer-based SB at the workplace and SB in leisure-time, future studies should capture self-reported records of daily working hours and use these data as an additional confounder to identify patterns of SB. How much time individuals spend sitting at the workplace and what kind of work they do can furthermore be taken into account as it may influence SB in their leisure-time.…”
Section: Discussionmentioning
confidence: 99%
“…The VO 2 max can be estimated applying a specific equation [85]. It has been used to asses cardiorespiratory fitness in several studies [86,87].…”
Section: Indirect Field Testsmentioning
confidence: 99%
“…1 Low cardiorespiratory fitness is also a strong risk factor for cardiovascular disease 2, 3 , diabetes 4-6 and all-cause mortality. 3,7,8 Cardiorespiratory fitness is affected by nonmodifiable factors such as genetic factors 9 , age and gender 10,11 as well as modifiable factors including physical activity 12 , sitting time 13 , body mass index 14 , smoking 15 , and medical conditions. 16 Among other modifiable factors, physical activity and sitting time are emerging concerns because of the current and prevalent change in life style.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that leisure time physical activity and sitting during leisure time have more influence on cardiorespiratory fitness. 12,13,17 Other studies claimed that workplace habits, where the employees spend most of their waking time, havestrong correlations with health outcomes. [18][19][20][21] Our study was designed to determine the relationship between each kind of domain-specific physical activity and sitting time with cardiorespiratory fitness among male workers.…”
Section: Introductionmentioning
confidence: 99%